2020
DOI: 10.1108/k-09-2019-0602
|View full text |Cite
|
Sign up to set email alerts
|

Three-way group decisions under hesitant fuzzy linguistic environment for green supplier selection

Abstract: Purpose The purpose of this paper is to propose a three-way group decision-making approach to address the selection of green supplier, by extending decision-theoretic rough set (DTRS) into hesitant fuzzy linguistic (HFL) environment, considering the flexible evaluation expression format of HFL term set (HFLTS) and the idea of minimum expected risk in DTRS. Design/methodology/approach Specifically, the authors first present the calculation method of the conditional probability and discuss the loss functions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…In [175], a group consensus decision-making model was developed to help choosing the best green supplier for electronics manufacturing. Ma et al [176] proposed a three-way group decision-making approach to address the selection of the green supplier by extending the decision-theoretic rough sets into hesitant fuzzy linguistic environment. Chen et al [177] applied the six sigma quality indices to the evaluation of suppliers based on their process yields and quality levels.…”
Section: Other Supplier Selection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [175], a group consensus decision-making model was developed to help choosing the best green supplier for electronics manufacturing. Ma et al [176] proposed a three-way group decision-making approach to address the selection of the green supplier by extending the decision-theoretic rough sets into hesitant fuzzy linguistic environment. Chen et al [177] applied the six sigma quality indices to the evaluation of suppliers based on their process yields and quality levels.…”
Section: Other Supplier Selection Methodsmentioning
confidence: 99%
“…Moreover, the interval type-2 fuzzy sets and the intuitionistic fuzzy sets are also frequently used by researchers to deal with the vagueness and uncertainty of performance evaluations in GSES, which have appeared in 10 and 9 articles, respectively. Considering that decision makers incline to give their opinions with linguistic expressions, some linguistic computing methods have been utilized in the green supplier evaluation process recently, which include the intervalvalued intuitionistic uncertain linguistic set [62,91,156], the hesitant fuzzy linguistic term set [174,176], the cloud model theory [79,138], and the interval 2-tuple linguistic variable [147].…”
Section: Green Supplier Evaluation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sen et al (2018) applied intuitionistic-TOPSIS, intuitionisticmulti-objective optimization method by ratio analysis (MOORA) and intuitionistic-GRA. Ma et al (2020) proposed an extension of the rough set into the hesitant fuzzy linguistic set to SVS. Liang and Chong (2019) adopted hesitant fuzzy qualitative flexible multiple criteria (QUALIFLEX) for green SS for a mega project in China.…”
Section: Sustainable Vendor Assessmentmentioning
confidence: 99%
“…Gao et al [ 9 ] suggested an innovative probabilistic linguistic consensus decision framework based on the consensus measure and feedback mechanism to choose the optimal green supplier. Ma et al [ 10 ] brought a three-way group decision methodology by extending a decision–theoretic rough set into hesitant fuzzy linguistics to evaluate the most-satisfying supplier. Further, in order to comprehensively analyze the literature on green supplier selection, Zhang et al [ 11 ] developed a comprehensive overview of green supplier evaluation and selection through summarizing and analyzing the research from 2009 to 2020 and providing some novel research directions and challenges.…”
Section: Introductionmentioning
confidence: 99%